Tools to study microbial iron homeostasis and oxidative stress: current techniques and methodological gaps - Strzelecki, Patryk; Nowicki, Dariusz (Frontiers in Molecular Biosciences, 2025)
Iron is a vital nutrient for both microbial pathogens and their eukaryotic hosts, playing essential roles in stress adaptation, symbiotic interactions, virulence expression, and chronic inflammatory diseases. This review discusses current laboratory methods for iron detection and quantification in microbial cultures, host-pathogen models, and environmental samples. Microbial pathogens have evolved sophisticated specialized transport systems, iron acquisition strategies to overcome its limitation, including siderophore production, uptake of heme and host iron-binding. These iron-scavenging systems are closely linked to the regulation of virulence traits such as adhesion, motility, toxin secretion, and biofilm formation. In ESKAPEE pathogens (Enterococcus faecium, Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter baumannii, Pseudomonas aeruginosa, Enterobacter spp. and Escherichia coli), iron limitation enhances biofilm development, which protects bacteria from antibiotics and immune responses and promotes persistent infections. Even worse, pathogens can also manipulate host iron metabolism, exacerbating inflammation and disease progression. Although iron is indispensable for microbial growth, excessive intracellular iron promotes reactive oxygen species generation, causing oxidative damage and ferroptosis-like cell death. Understanding the dual role of iron as both a nutrient and a toxic agent highlights its importance in infection dynamics. We provide a critical overview of existing analytical techniques and emphasize the need for careful selection of methods to improve our understanding of microbial iron metabolism, host-pathogen interactions, and to support the development of new therapeutic and environmental monitoring strategies.